Diverse biologies and experiential continuities: did the ancient Chinese know that Qinghao had anti-malarial properties? - Hsu, E (Canadian Society for the History of Medicine, 2009)
This article treats Chinese medical theories and concepts as cultural constructs that arose as much from practice-oriented concerns as from socio-political negotiations within the medical field. It further explores the interface of the biological and cultural. It is often futile to investigate how Chinese medical descriptions relate to biological processes, because the local biologies that the Chinese physicians recognized in the past and continue to describe in the present, are contested by mainstream medicine, but recent bioscientific research on the anti-malarial properties of the Chinese medical drug qinghao opens up new avenues for the historian. To be sure, no attempt is made to equate ancient nosologies to modern ones, nor to justify the cultural through the biological. In order to avoid the pitfalls of simple equations, this article takes the experiential not merely as a subjective but as an inter-subjective reality that mediates the biological and cultural. The findings are striking: once one reads the Chinese medical texts as reporting on the experiential, one of their many possible readings is that they provide concrete descriptions of morbid conditions that also the contemporary mainstream physician recognizes.